Minerals Industry Salary Survey (Society for Mining, Metallurgy & Exploration, 1992)
In its April 1991 issue, MINING ENGINEERING published a salary survey form asking for information relating to engineering and management jobs in the minerals industry. 1038 of these forms were filled out and returned, most of them being received in the magazine's offices at SME headquarters before the end of June 1991. An SME volunteer took on the task of tabulating and analyzing data from the forms, but the press of other business interfered with this work, and publication has been delayed until this issue of MINING ENGINEERING. Appreciation is extended to SME members who took the time to fill out and return the salary survey forms, and our apologies go to MINING ENGINEERING'S readers for the delay in publication. Of the total number of forms received, more than 97% were from SME members. The geographic distribution of the respondents closely mirrored that of SME membership as a whole, about 50% being from the Society's Western Region, 19% from the Central Region, and 23% from the Eastern Region. About 8% were from outside the US. Average salaries for each of the four geographic areas ranged between $55,000 and $60,000, with the highest average in Eastern Region (Fig. 1). Respondents were asked to answer a number of questions formulated to determine if there are significant differences in salaries based on the type of organization for which they work. As indicated by Table 1, salary averages at mining companies do not vary markedly with the size of the company: • Large companies, defined as those having more than $1 billion in annual sales, accounted for just over 16% of the returns. Their average salary was $61,840 per year.